Functional nanofibrous scaffolds combined with stem cells for bone and cartilage tissue engineering - Neves, N. M. (2015)
The use of temporary scaffolds in Advanced Therapies and in particular of Tissue Engineering is one of the key issues to regenerate tissue defects. The scaffolds should be specifically designed to create environments that promote tissue development and not merely to support the maintenance of communities of cells. Many biomaterials have been proposed to produce scaffolds aiming the regeneration of a wealth of human tissues. We have a particular interest in developing systems based in nanofibrous biodegradable polymers1,2. Those demanding applications require a combination of mechanical properties, processability, cell-friendly surfaces and tunable biodegradability that need to be tailored for the specific application envisioned. In our approach, we combine the temporary scaffolds populated with therapeutically relevant communities of cells to generate a hybrid implant. We are exploring the use of adult MSCs3 , namely obtained from the bone marrow for the development of autologous-based therapies. We also develop strategies based in extra-embryonic tissues, such as amniotic fluid (AF) and the perivascular region of the umbilical cord4 (Whartonâ s Jelly, WJ). Those tissues offer many advantages over both embryonic and other adult stem cell sources. The comparatively large volume of tissue and ease of physical manipulation facilitates the isolation of larger numbers of stem cells. Fetal stem cells seem having more pronounced immunomodulatory properties than adult MSCs. This allogeneic escape mechanism may be of therapeutic value, because the transplantation of readily available allogeneic human MSCs would be preferable as opposed to the required expansion stage (involving both time and logistic effort) of autologous cells.